2022
DOI: 10.1002/jcop.22950
|View full text |Cite
|
Sign up to set email alerts
|

Organizational cultures that support community: Does the competing values framework help us understand experiences of community at work?

Abstract: Recent evidence has shown that when employees experience perceptions of community at work (i.e., a sense of community and a sense of community responsibility), psychological well‐being and behavioral engagement improve (e.g., greater job engagement, organizational citizenship, and leadership). Recent evidence also shows that experiences of community, as a motivational state, are better able to predict employee outcomes compared to a series of factors that have long been studied in the general management (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Employees see work as a component of their holistic life and therefore want managers who care about them and want to help them achieve their aspirations. These findings are consistent with other research (Boyd & Larson, 2022) which showed that experiences of the community are more likely built in proximal environments as opposed to the distal environment of the organization as a whole. They also highlight that HR professionals, and managers, should pay particular attention to building organizational cultures of community within work units.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Employees see work as a component of their holistic life and therefore want managers who care about them and want to help them achieve their aspirations. These findings are consistent with other research (Boyd & Larson, 2022) which showed that experiences of the community are more likely built in proximal environments as opposed to the distal environment of the organization as a whole. They also highlight that HR professionals, and managers, should pay particular attention to building organizational cultures of community within work units.…”
Section: Discussionsupporting
confidence: 93%
“…The second study was designed as a quantitative assessment of cultural types that can lead to experiences of community, and it included executives, system leaders, mid‐managers, and line employees. The second study is reported in a separate manuscript (Boyd & Larson, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…We also urge a more focused examination of where EPAs best fit within the training continuum of residency and fellowship training. At minimum, department chairs and program directors need to periodically undertake value and/ or culture scans [28][29][30] of their residencybased learning environments to better capture the underlying ethical and structural drivers that enrich and sustain what is, after all, a professionally oriented and values-based moral enterprise. 31 While competencies and EPAs are important adjuncts to learning, they are not a substitute for values.…”
Section: What About the "P" In Epas?mentioning
confidence: 99%